Cost-effectiveness analysis of treating transplant-eligible multiple myeloma patients in Macedonia - Qerimi V; Kapedanovska Nestorovska A; Sterjev Z; Genadieva-Stavric S; Suturkova L (Dove Medical Press, 2018)
Vjollca Qerimi,1,2 Aleksandra Kapedanovska Nestorovska,1 Zoran Sterjev,1 Sonja Genadieva-Stavric,3 Ljubica Suturkova1 1Faculty of Pharmacy, Ss. Cyril and Methodius University in Skopje, Skopje, Macedonia; 2Institute of Public Health, Medical Decision Making and Health Technology Assessment, Department of Public Health, Health Services Research and Health Technology Assessment, UMIT – University for Health Sciences, Medical Informatics and Technology, Hall in Tirol, Austria; 3Medical Faculty, University Hematology Clinic, Skopje, Macedonia Purpose: A decision-analytic model was developed to study the impact of induction regimens vincristine, adriamycin, dexamethasone (VAD); thalidomide, dexamethasone (TD); and bortezomib, dexamethasone (BorD), followed by autologous stem cell transplantation (ASCT) for treating multiple myeloma (MM) patients in Macedonia. Additionally, a cost-effectiveness analysis (CEA) of treatment sequences to predict health effects and costs of different treatment sequences was performed.Methods: Model strategies were based on a previously published study for treating patients with MM in Macedonia. The data on disease progression and treatment effectiveness were obtained from the published reports of randomized clinical trials (GIMEMA M-B02005, IFM 2005-01). Utility parameters were extracted from the literature. To compare treatment combinations, a decision tree model was developed. Additionally, a cost analysis for one-time per-protocol costs was performed from a Macedonian national health care perspective. The incremental cost-effectiveness ratios (ICERs)/quality-adjusted life years (QALYs) gained for 1-, 10-, and 20-year time horizons were determined. Costs and health outcomes were discounted to evaluate the effects of time in the model.Results: The one-time costs of BorD (EUR 5,656) were higher compared to VAD (EUR 303) and TD (EUR 329), increasing the overall costs for BorD. Thus, the BorD combination dominated in the baseline results (1 and 10 years) and the ICER for TD vs. VAD was EUR 7,564/QALY (20 years, undiscounted model). However, in the discounted 20-year model, BorD showed an ICER of EUR 138,747/QALY gained for BorD vs. TD.Conclusion: The CEA performed indicated that considering 1-year time horizon costs, VAD may be a cost-effective alternative vs. TD or BorD. However, for the longer period (10 or 20 years) including the discounting of future costs and outcomes, the TD and BorD combinations showed higher health benefits in terms of QALYs and more cost-effective vs. VAD. These results should be considered as supportive evidence by decision-makers and providers when deciding on the most cost-effective induction treatment strategy prior to ASCT in MM patients. Keywords: decision-analytic modeling, decision tree, multiple myeloma, incremental cost-effectiveness ratio, transplant-eligible